Warunki krytyki metodologicznej prac badawczych - Piekarski, Jacek; Urbaniak-Zając, Danuta; Pasikowski, Sławomir (Krytyka metodologiczna w praktyce tworzenia wiedzy, 2019)
The chapter presents a model of research critique using the idea of deviations from the pattern of methodological correctness. The author introduces the concept of two categories of such deviations: from the local standard and from the generalized criterion. Both refer to the concept of visibility, which co-determines the scope of the response on the side of the sender as well as of the receiver of the empirical report. As a consequence, the author proposed a model of methodological critique that refers to the awareness of failures, defining the conditions of visibility of deviations, and methodological rigor in the discipline, which determines the scope of environmental legitimacy of these deviations. The model makes it possible to predict the behaviour of the creator, the recipient and the disciplinary community in which the report is presented, as well as to characterize the persuasiveness of scientific communication by the empirical reports.